Anode protection layer

By forming a double-layer protective layer on the rubidium metal or rubidium metal alloy layer of the rubidium cell, the metal and non-metal alloy of the first layer react with the rubidium metal, and the ceramic or glass material of the second layer provides high ionic conductivity and low electron conductivity, the problems of rubidium metal electrolysis and dendritic formation are solved, and the performance and life of the battery are improved.

JP7650858B2Active Publication Date: 2025-03-25GERION TECH PTY LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022500540
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-10
Filing Date
2020-07-09
Publication Date
2025-03-25
Estimated Expiration
2040-07-09

AI Technical Summary

Technical Problem

In the prior art, when using rubidium batteries, rubidium metal is easily electrolyzed in the battery to form an impedance layer, resulting in a degradation of battery performance, and easy formation of lithium dendrites and deposition, resulting in short circuits and shortening of battery life.

Method used

A double-layer protective layer structure is adopted, wherein the first layer is composed of metal and non-metallic materials that can be with rubidium metal alloy, and the second layer is a ceramic or glass material with low electron conductivity and high ionic conductivity, which is formed on the rubidium metal or rubidium metal alloy layer to reduce the direct contact between rubidium metal and the electrolyte.

Benefits of technology

It effectively reduces the electrolysis and dendritic formation of rubidium metal, reduces the internal impedance of the battery, extends the service life of the battery, and improves the cycling stability and energy density of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007650858000001
    Figure 0007650858000001
  • Figure 0007650858000002
    Figure 0007650858000002
  • Figure 0007650858000003
    Figure 0007650858000003
Patent Text Reader

Abstract

1. An electrochemical cell assembly comprising: at least one or more electrochemical cells, a cathode comprising an electrochemically active material; - an anode comprising an alkali metal layer or an alkali metal alloy layer and a protective layer containing a first layer and a second layer, wherein the first layer comprises a metal and / or a non-metal that alloys with the alkali metal and is formed on the alkali metal layer or the alkali metal alloy layer, and the second layer is deposited on the first layer, and the second layer is -5 Scm -1 an anode, which is an ionically conductive layer having an electronic conductivity of less than an electrolyte; and at least one or more electrochemical cells comprising: The cell assembly further comprises means for applying pressure to the at least one or more electrochemical cells.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrochemical cell. The present invention also relates to a method of forming an electrochemical cell, and in particular to a method of forming a coating on an anode of an electrochemical cell. [Background technology]

[0002] Electrodes containing alkali metals and alkaline earth metals have been used in both primary and secondary electrochemical cells. In particular, lithium has proven to be a desirable material for forming electrodes, as it is a lightweight material that can provide high energy density. This can allow for the construction of cells suitable for a wide range of applications, including those in which minimizing the weight of the cell is of great importance. In lithium-sulfur cells, for example, lithium metal foil may be used as the anode of the cell.

[0003] However, despite the advantages offered by the use of such electrodes, alkali and alkaline earth metals have certain drawbacks when used in electrochemical cells. Using lithium metal foil as an example, lithium is electrolytically charged in the cell. quality This can form a resistive layer on the electrode, reducing battery performance over time. Lithium dendrites and / or modulus deposits can form on the surface of the lithium metal foil during cycling, which can lead to short circuits and reduced cycling performance, and ultimately reduced cell life.

[0004] In view of the above difficulties, it may be desirable to include a protective layer on the surface of the anode. Various protective layers have been proposed. Such protective layers are intended to provide a barrier between the surface of the anode and the bulk electrolyte. quality It is necessary to conduct alkali metal ions while reducing or preventing contact between the anode and the electrolyte. For example, an alloy layer on top of the anode has been proposed as a means of improving the cycling or capacity characteristics of the cell. However, the alkali metal alloy layer becomes degraded over time and can become electrolytically unstable. qualityThe alkali metal may react with the alloy layer, resulting in the formation of a resistive layer on top of the electrode. Alkali metal plating on the alloy layer may also be observed, along with uneven peeling.

[0005] Ceramic materials have also been proposed as candidates for forming a protective layer on the anode. U.S. Patent No. 6,025,094 discloses a negative electrode having an alkali metal layer and a glassy or amorphous protective layer coating the alkali metal layer, the protective layer conducting alkali metal ions. However, the use of a ceramic layer can increase the charge transfer resistance of the anode, which can lead to uneven peeling and plating of the alkali metal, and alkali metal deposition on top of the protective layer. [Brief description of the drawings]

[0006] [Figure 1] 1 shows an SEM image of the surface of a lithium metal electrode.

[0007] [Diagram 2] 1 shows an SEM image and an impedance graph of a lithium anode having an alloy layer formed on its surface.

[0008] [Diagram 3] 1 shows an SEM image and an impedance graph of a lithium anode having a ceramic layer formed on its surface.

[0009] [Figure 4] 1 shows digital photographs and SEM images of a protected lithium anode after completion of a lithium plating step under applied forces of 0 MPa, 0.5 MPa, and 1 MPa, according to an embodiment of the present invention.

[0010] [Diagram 5] 1 shows digital photographs, SEM images, and cross-sectional views of a protected lithium anode after a lithium stripping step according to an embodiment of the present invention.

[0011] [Figure 6]1 shows digital photographs and SEM images of a protected lithium anode according to an embodiment of the present invention.

[0012] [Figure 7] 1 shows electrochemical data for protected lithium anodes according to embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Before describing particular embodiments of the present invention, it is to be understood that the disclosure is not limited to the particular cells, methods, or materials disclosed herein. It is also to be understood that the terminology used herein is used only to describe particular embodiments and is not intended to be limiting; similarly, the scope of protection is defined by the claims and their equivalents.

[0014] In describing and claiming the cells and methods of the present invention, the following terminology is used. The singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates otherwise. Thus, for example, reference to "an anode" includes reference to one or more of such elements.

[0015] According to a first aspect of the present invention there is provided an electrochemical cell assembly comprising: At least one or more electrochemical cells, a cathode comprising an electrochemically active material; - an anode comprising an alkali metal or alkali metal alloy layer and a protective layer comprising a first layer and a second layer, the first layer comprising a metal and / or a non-metal that alloys with the alkali metal being formed on the alkali metal or alkali metal alloy layer, the second layer being deposited on the first layer, -5 S cm -1 an anode comprising an ionically conductive layer having an electronic conductivity of less than -electrolytic quality and at least one or more electrochemical cells comprising: The cell assembly further comprises a means for applying pressure to the at least one or more electrochemical cells.

[0016] According to another aspect of the present invention, there is provided an electrochemical cell assembly comprising: At least one or more electrochemical cells, a cathode comprising an electrochemically active material; an anode comprising an alkali metal or alkali metal alloy layer and a protective layer comprising a first layer and a second layer, the first layer comprising a metal and / or a non-metal that alloys with the alkali metal and formed on the alkali metal or alkali metal alloy layer, the second layer being deposited on the first layer and comprising an ion-conducting layer comprising at least one of a conductive polymer, a ceramic or glass material, a polymer and ceramic composite material; -electrolytic quality and at least one or more electrochemical cells comprising: The cell assembly further comprises a means for applying pressure to the at least one or more electrochemical cells.

[0017] According to another aspect of the present invention, there is provided a method of forming the electrochemical cell assembly described above, the method comprising the steps of:

[0018] a) providing an alkali metal or alkali metal alloy layer;

[0019] b) contacting at least one metal and / or nonmetal that forms an alloy with an alkali metal with the alkali metal or alkali metal alloy layer to form a continuous first layer;

[0020] c) 10 on the surface of the first layer -5 S cm -1 and depositing an ionically conductive layer having an electronic conductivity less than 100 nm to form a continuous second layer, steps a) to c) forming an anode;

[0021] d) Electrolysis quality and

[0022] e) providing a cathode, wherein steps a) through e) form an electrochemical cell;

[0023] f) applying a means for supplying a force to at least one cell in accordance with steps a) to e).

[0024] As used throughout this specification, the term "anode" refers to the negative electrode in an electrochemical cell, i.e., the electrode where oxidation occurs during charging of the cell. As used throughout this specification, the term "cathode" refers to the positive electrode in an electrochemical cell, i.e., the electrode where reduction occurs during charging of the cell.

[0025] The protective layer according to the invention may comprise two sub-layers. Preferably, the protective layer comprises a first layer and a second layer, the second layer being a layer that protects the electrolytic quality The protective layer is in direct contact with the alkali metal. Cells in which the protective layer comprises more than two layers may also be envisaged. For example, the protective layer may comprise two or more layers capable of alloying with an alkali metal. Additionally or alternatively, the protective layer may comprise two or more ion-conducting layers. Other suitable layers may also be included within the protective layer. Preferably, the protective layer comprises a metal and / or non-metal that alloys with the alkali metal and is formed on the alkali metal or alkali metal alloy layer, and a second layer is deposited on the first layer, and 10 -5 S cm -1 The ionically conductive layer has an electronic conductivity of less than 100 nm.

[0026] In forming a protective layer comprising the first and second layers described herein, the inventors have provided an anode coating that may have a beneficial effect on cell performance. Such a protective layer may have improved properties, e.g., reduced interfacial resistance, compared to a cell that includes several different coatings on the anode. In combination, the first and second layers may have a thickness of 2 nm to 10,000 nm, preferably 10 nm to 4,000 nm, more preferably 100 nm to 5,000 nm, e.g., 500 nm to 3,000 nm. By maintaining a relatively thin thickness of the individual layers, and the relatively thin thickness of the combination of layers, the tendency of the protective layer to crack may be reduced or eliminated. Avoidance or minimization of cracking may be beneficial with respect to cell life.

[0027] The protective layer or coating according to the invention may provide improved battery performance. For example, the electrochemical cell according to the invention may provide improved cycle and capacity life. Without wishing to be bound by any theory, it is believed that the protective layer allows for uniform stripping of alkali metals (e.g., lithium or sodium) from anodes containing such metals during discharge. Non-uniform stripping may have the consequence of pitting and / or cracking of the electrode, which may reduce the life and / or performance of the cell. Non-uniform stripping and plating may also result in the formation of alkali metal dendrites, which may cause safety hazards and short circuit risks, and may reduce the energy density of the cell. Figure 1 shows non-uniform plating and stripping on the surface of a lithium metal electrode. Areas of high surface area lithium formation may occur during deposition along with pitting of the electrode during stripping. Surface pitting may be seen in Figure 1.

[0028] Protective layers that allow for the formation of an alloy with an alkali metal, such as lithium or sodium, may provide benefits such as reduced charge transfer resistance when the protective layer is applied, but such alloy layers may also reduce the electrolytic resistance over time. quality reacts with the electrolyte, causing an increase in resistance and electrolysis. qualityThis can result in depletion of the alloy layer. Significant alkali metal plating can also occur on top of the alloy layer, along with the formation of cracks and / or pitting on the surface. The use of a ceramic protective layer alone can also increase charge transfer resistance, while also resulting in non-uniform alkali metal peeling and / or plating. Thus, either an alloy protective layer alone, or a ceramic protective layer alone, may not be an adequate means to provide an improved anode structure. The inventors have surprisingly found that a protective layer having a first layer and a second layer as defined herein can result in uniform peeling from the alkali metal layer. The inventors have also found that alkali metal deposition can occur directly beneath the alloy layer during charging. Without wishing to be bound by any theory, this may be the result of reduced interfacial resistance compared to other protective systems. This may be due to the interface between the first layer and the second layer being very tight, meaning that alkali metal nucleation occurs preferentially between the current collecting layer and the alloy layer. Deposition of an alkali metal, such as lithium, directly beneath the alloy layer can beneficially provide a more uniform deposition and provide a smooth anode surface. The formation of cracks and voids on the anode surface may be minimized or prevented. The inventors have also found a reduction in impedance of the anode according to the invention when compared to a comparable unprotected anode. The inventors have also found a reduced impedance compared to anodes having either an alloy protective layer alone or a ceramic protective layer alone. Without wishing to be bound by any theory, it is believed that this reduced impedance may allow deposition / peeling to occur under the protective layer.

[0029] The electrochemical cell according to the present invention can be any suitable alkali metal or alkaline earth metal based cell. The anodes described herein can be combined with a variety of positive electrode materials, in particular with any high energy cathode. Non-limiting examples of electrochemical cells include lithium or sodium sulfur cells, lithium or sodium ion cells (e.g., lithium or sodium NMC cells), or lithium or sodium air cells (e.g., lithium or sodium O2 cells). Preferably, the electrochemical cell is a lithium sulfur cell or a lithium ion cell. Alternatively, the cell can include an alkaline earth metal, such as magnesium, instead of lithium or sodium. Each electrochemical cell comprises an anode and a cathode, and an electrolyte that exists between the anode and the cathode. quality may include.

[0030] The electrochemical cell according to the invention comprises an alkali metal or alkali metal alloy layer. The alkali metal or alkali metal alloy layer forms part of the anode. Any suitable alkali or alkaline earth metal or alkali metal alloy may be coated with a protective coating as described herein. For example, the alkali metal may be lithium metal or lithium metal alloy. Preferably, the anode comprises a foil formed of lithium metal or lithium metal alloy. Examples of lithium alloys include lithium aluminum alloy, lithium magnesium alloy, and lithium boron alloy. Preferably, lithium metal foil is used. Alternatively, the anode may comprise sodium metal or sodium metal alloy, or magnesium metal or magnesium metal alloy. The alkali metal or alkaline earth metal or alkali metal alloy layer may have a thickness of 500 nm to 200 μm, preferably 1 μm to 100 μm, for example 25 μm to 75 μm.

[0031] The anode may further comprise an optional current collector. A separate current collector may be combined with an alkali metal or alkaline earth metal layer to form a current collector layer, in which the alkali metal or metal alloy layer is in electrical contact with the current collector. If present, the separate current collector may comprise a conductive metal material, e.g., a metal foil, metal sheet, or metal mesh. Current collectors in lithium or sodium cells may typically be composed of a metal conductor other than the first metal, e.g., other than lithium or sodium. Preferably, the metal selected is substantially inert so that the current collector does not affect the cell chemistry. Examples of suitable metals include aluminum, copper, or nickel. In a preferred embodiment, the current collector comprises copper foil. The alkali metal may be formed or placed on the current collector to form the current collector layer. Alternatively, a separate current collector may not be present in the anode structure.

[0032] The protective layer comprises a first layer on the alkali metal or alkali metal alloy layer. Preferably, the first layer is a continuous layer, i.e., it covers the entire surface of the alkali metal or alkali metal alloy layer. The first layer is in intimate contact with the alkali metal or alkali metal alloy layer. The first layer comprises at least one metal and / or nonmetal capable of forming an alloy with an alkali metal, such as lithium or sodium. The term "alloy" refers to a combination of two or more metals, or a combination of one or more metals with other nonmetallic elements. Examples of suitable alloying metals and nonmetals include aluminum, gallium, boron, indium, zinc, carbon, silicon, germanium, tin, lead, antimony, silver, gold, sodium, potassium, magnesium, calcium, and mixtures thereof. Examples of base lithium alloys that may be included in the alloy layer of a lithium-based cell include Li n Al x , Li n Zinc x , Li n Ga x , Li n In x , Li n C x , Li n C x , Li nS x , Li n Ge x , Li n Sn x , Li n Pb x , Li n Sb x , Li n Ag x , Li n Au x , Li n Na x , Li n K x , Li n Mg x , Li n Ca x , where n may be 0.1 to 20, for example, 1 to 5, and x may be 0.5 to 10, for example, 1 to 5. For example, the lithium-indium alloy that can be formed in the first layer is Li 0.3 In 1.7 , LiIn, Li5In4, Li3In2, Li2In and Li 13 In3, although further alloys may additionally / alternatively be formed. One or more base metal alloys may be included in the alloy layer. In a preferred embodiment, the alloy layer includes a lithium-indium alloy. Alternatively, the alloy layer includes a lithium-zinc alloy. The alloy layer may include a sodium-indium alloy or a sodium-zinc alloy. Alloying of the alloying metal and / or non-metal with the alkali metal may occur during cycling of the cell. Alternatively, some alloying may occur during manufacturing of the cell.

[0033] The first layer is electronically conductive. -5 Scm -1 Greater than, preferably 10 -3 Scm -1 Greater than 10, preferably -1 Scm -1 Larger, e.g., 1Scm -1 The electronic conductivity of the first layer may allow an alloying reaction to occur between the alkali metal or alkali metal alloy layer and the first layer. The electronic conductivity may also be used in the cell, e.g., in the electrolytic quality In the first layer, an alloying reaction may be allowed to occur between the first layer and the alkali metal ions present. Electronic conductivity may be measured by any suitable method.

[0034] The first layer may have a high alkali metal diffusivity, i.e., allows alkali metal ions to pass through the layer. -15 cm 2 s -1 Greater than, preferably 10 -10 cm 2 s -1 Greater than 10, preferably -8 cm 2 s -1 Greater than, for example, 10 -7 cm 2 s -1 The first layer may have a higher initial alkali metal diffusivity in its original form, i.e., before cycling. Alternatively, the first layer may have a lower alkali metal diffusivity, e.g., 10 -15 cm 2 s -1 During cycling, the alkali metal content in the first layer may change due to, for example, charging or discharging points. Thus, when the alkali metal contained in the first layer is stripped during cycling, the diffusivity of the alkali metal may increase. The high diffusivity of the "intermediate" species forming the first layer may allow spontaneous and uniform stripping from the alkali metal in the current collecting layer.

[0035] The first layer is ionically conductive, i.e., it allows alkali metal ions to pass through the layer. Thus, during cell discharge, alkali metal ions pass through the coating to the electrolytic quality Similarly, when the cell is charged, the electrolyte quality The alkali metal ions from the can diffuse and migrate through the coating and deposit beneath the coating as an alkali metal, e.g., lithium or sodium. -9 Scm -1Greater than, preferably 10 -8 Scm -1 Greater than, preferably 10 -7 Scm -1 Greater than 10, preferably -6 Scm -1 Greater than, for example, 10 -5 Scm -1 The ionic conductivity may be greater than or equal to 100%. The ionic conductivity may be measured by any suitable method.

[0036] The first layer may have high ionic conductivity and / or high alkali metal diffusivity. In one embodiment, the first layer has a 10 -9 Scm -1 It has an ionic conductivity greater than 10 -15 cm 2 s -1 It may have a greater alkali metal diffusivity.

[0037] The first layer is capable of storing a certain amount of alkali metal. The amount of alkali metal stored in the first layer varies at different stages during the cycle of the cell. The total amount of alkali metal that can be stored in the first layer may be less than 60%, preferably less than 30%, preferably less than 10%, for example less than 5%, of the electrochemical alkali metal storage capacity of the electroactive material in the cathode. During charging of the electrochemical cell, the first layer may become saturated with alkali metal. As charging progresses toward completion, formation (nucleation and growth) of elemental alkali metal may occur beneath the alloy layer.

[0038] The thickness of the first layer can be from 1 nm to 5000 nm, preferably from 10 nm to 1000 nm, for example, from 100 nm to 500 nm.

[0039] The protective layer further comprises a second layer deposited on the first layer. The second layer is in intimate contact with the first layer. Preferably, the second layer is a continuous layer, i.e., it covers the entire surface of the first layer. The second layer may have a uniform thickness. The thickness of the second layer may be 1 nm to 1000 nm, preferably 10 nm to 500 nm, for example 100 nm to 250 nm.

[0040] The second layer is ionically conductive, i.e., it allows alkali metal ions to pass through the layer. Thus, during cell discharge, alkali metal ions pass through the coating to the electrolytic quality Similarly, when the cell is charged, the electrolyte quality Alkali metal ions from the 100% Cr-Al2O3 can migrate through the coating and deposit beneath the coating as an alkali metal, e.g., lithium or sodium. Thus, the second layer can provide a protective function while allowing the passage of alkali metal ions during charging and discharging. The second layer can be 100% Cr-Al2O3. -9 Scm -1 Greater than, preferably 10 -8 Scm -1 Greater than, preferably 10 -7 Scm -1 Greater than 10, preferably -6 Scm -1 Greater than, for example, 10 -5 Scm -1 It may have a greater ionic conductivity.

[0041] The second layer has low electronic conductivity, i.e., is substantially electronically insulating. By including a layer of low electronic conductivity, Li + and Na + The second layer can be formed by 10 -5 Scm -1 Less than 10 -8 Scm -1 Less than 10, more preferably -10 Scm -1 In one embodiment, the electronic conductivity is less than 10 -12 Scm -1 is less than.

[0042] The second layer may include at least one of a ceramic or glass material, a polymeric material, a composite material of polymer and ceramic, and combinations thereof. Suitable ceramic or glass materials include, for example, one or more elements selected from lithium, oxygen, phosphorus, nitrogen, sulfur, boron, selenium, fluorine, chlorine, bromine, or iodine. Suitable ceramic materials may be stoichiometric or non-stoichiometric. The ceramic material may be an oxynitride, sulfide, phosphate, oxide, oxysulfide, thiophosphate, borate, oxyborate, borohydride, silicate, aluminate, or thioaluminate compound, or combinations thereof. Examples of suitable materials include lithium oxynitride, lithium sulfide, lithium phosphate, lithium oxide, lithium oxysulfide, lithium thiophosphate, lithium borate, lithium oxyborate, lithium borohydride, lithium silicate, lithium aluminate, and lithium thioaluminate, or combinations thereof. Alternatively, the material may be selected from one or more of sodium oxynitride, sodium sulfide, sodium phosphate, sodium oxide, sodium oxysulfide, sodium thiophosphate, sodium borate, sodium oxyborate, sodium borohydride, sodium silicate, sodium aluminate, and sodium thioaluminate. The ceramic material may be an amorphous material.

[0043] Examples of suitable ceramic materials include LiPON, LLZO, LATP, LGPS, LPS, and LAGP. LiPON, LLZO, LATP, LGPS, LPS, and LAGP are examples of materials that are also useful as solid conductive electrolytes. Further examples of conductive ceramic or glass materials include Li2S-P2S5-LiI, Li2S-SiS2-LiI, Li2S-SiS2-Li3PO4, Li2O-P2O5-Li2SO4, Li2O-B2O3-LiI, Li2O-Al2O3-B2O3, Li2O-Al2O3-SiO2, and Li2O-SiO2-B2O3.

[0044] Particularly preferred ceramic materials are lithium oxides, such as lithium oxynitride. LiPON is an example of an amorphous non-stoichiometric lithium oxynitride phosphate that has low electronic conductivity and high ionic conductivity. Exemplary values ​​for electronic and ionic conductivity of LiPON are 10 -12 Scm -1 and 10 -6 Scm -1 This is the area.

[0045] The second layer may include a conductive polymer material, such as an ion-conducting polymer. Additionally or alternatively, the second layer may include a polymer material having an alkali metal salt distributed within the polymer material. This may provide or increase ionic conductivity within the polymer. The second layer may alternatively or additionally include a polymer-ceramic composite material. The polymer-ceramic composite material may include ceramic particles bonded together by at least one polymer material. The polymer or polymers used to form the polymer-ceramic composite material may have inherent alkali metal ion conductivity or may be mixed with an alkali metal salt.

[0046] For example, the polymeric material may include a lithium salt (e.g., LiTFSI) dissolved within the polyethylene oxide phase. Further examples of lithium salts include lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium nitrate, lithium perchlorate, lithium trifluoromethanesulfonimide, lithium bis(oxalate)borate, and lithium trifluoromethanesulfonate. Suitable sodium salts include sodium hexanoate, sodium hexafluoroarsenate, sodium nitrate, sodium perchlorate, sodium trifluoromethanesulfonimide, sodium bis(oxalate)borate, and sodium trifluoromethanesulfonate. Combinations of salts may also be used.

[0047] The polymer may include at least one functional group selected from the list of amine, amide, carbonyl, carboxyl, ether, thioether and hydroxyl groups, and mixtures thereof. Non-limiting examples of polymers include polyanhydrides, polyketones, polyesters, polystyrines, polyamides, polyimides, polyurethanes, polyolefins, polyvinyls. Non-limiting examples of ion-conducting polymers may include nitrogen- or sulfur-containing polymers, such as polypyrrole (PPY), polycarbazole, polyindole, polyazepines, polyanilines, polythiophenes, PEDOT, PPS. Further examples of ion-conducting polymers may include poly(fluorene), polyphenylene, polypyrene, polyazulene, polynaphthalene, poly(acetylene)s (PAC), and poly(p-phenylenevinylene) (PPV). In one embodiment, the polymeric material is polyethylene oxide.

[0048] Any suitable cell may be assembled using an anode according to the present invention. The anode may be coupled to any suitable cathode comprising a positive electrode material. For example, an anode and cathode comprising a mixture of an electroactive material and a solid conductive material may be used to electrochemically quality It may be placed in contact with

[0049] The cathode of the electrochemical cell comprises a suitable electroactive material. Optionally, the cathode may also comprise a current collector, for example a metal such as aluminum foil, copper foil, or nickel foil.

[0050] Examples of suitable positive electroactive materials for lithium based cells include lithium sulfide, sulfur, lithium oxide, oxygen, lithium cobalt oxide, lithium nickel cobalt manganate, lithium nickel aluminate, lithium nickel cobalt aluminate, lithium nickel manganate, lithium manganate, lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, lithium iron fluoride, and composites including combinations thereof. Examples of suitable positive electroactive materials for sodium based cells include sodium cobalt oxide, sodium vanadate, sodium manganate, sodium nickel cobalt manganate, sodium chromate, sodium iron phosphate, sodium fluorophosphate, sodium iron fluoride, and composites including combinations thereof.

[0051] For lithium-sulfur cells, the cathode may include a mixture of an electroactive sulfur material and a conductive material. The mixture forms an electroactive layer, which may be placed in contact with a current collector. The electroactive material and the conductive material may form a matrix on the current collector. The electroactive sulfur material may include elemental sulfur, sulfur-based organic compounds, sulfur-based inorganic compounds, and sulfur-containing polymers. Preferably, elemental sulfur is used. In one embodiment, the cathode includes a sulfur-carbon composite. The cathode may include an electroactive sulfur material that may also be ionically conductive. This material may contain sulfur and additional elements such as Li, Na, Mg, P, N, Si, Ge, Ti, Zr, Sn, B, Al, F, Cl, Br, I, O, or any combination thereof. Examples of sulfur-containing materials that are also ionically conductive include LGPS, Li3PS4, or Li7P3S. 11 In one embodiment, the cathode can include a sulfur-carbon composite that is also ionically conductive.

[0052] The solid conductive material can be any suitable conductive material. Preferably, the solid conductive material can be formed from carbon. Examples include carbon black, carbon fiber, graphene, and carbon nanotubes. Other suitable materials include metals (e.g., flakes, filings, and powders) and conductive polymers. Examples of conductive polymers include polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylenevinylene, and poly(3,4-ethylenedioxythiophene). Preferably, carbon black is used. In one embodiment, when the cathode includes a sulfur-carbon composite, no additional solid conductive material may be present in the cathode.

[0053] The cathode is an ionically conductive material, specifically solid Li + Or Na + The ion conductive material may further comprise an ion conductor. -7 Greater than S / cm, e.g. 10 -6 The cathode may have a bulk ionic conductivity of greater than Li3PS4 or Li x P y S zIn some embodiments, the lithium ion conductive material includes an electroactive ion conductive material such as lithium ion conductive material, no additional ion conductive material may be present. In some embodiments, the lithium ion conductive material includes a ceramic material. The ceramic material may have a crystalline, polycrystalline, partially crystalline, or amorphous structure. Suitable ceramic materials include, but are not limited to, oxides, carbonates, nitrides, carbides, sulfides, oxysulfides, and / or oxynitrides of metals and / or metalloids. In some cases, the ceramic material includes lithium or sodium. Non-limiting examples of suitable solid electrolytes having sufficient ionic conductivity include combinations of various lithium compounds, such as lithium oxides (e.g., Li2O, LiO, LiO2, LiRO2, where R is scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and / or lutetium), lithium carbonate (Li2CO3), lithium nitride (e.g., Li3N), lithium oxysulfide, lithium oxynitride, lithium garnet-type oxides (e.g., Li7La3Zr2O 12 ), Li 10 GeP2S 12 Lithium-containing ceramic materials, including lithium oxylite, lithium phosphate, lithium silicate, lithium germanate, lithium lanthanum oxide, lithium titanium oxide, lithium borosulfide, lithium aluminosulfide, lithium phosphosulfide, lithium silicate, lithium borate, lithium aluminate, lithium phosphate, lithium halides, and combinations of the above, may be used. In some cases, the ceramic material includes lithium oxide, lithium nitride, or lithium oxysulfide. In some embodiments, the ceramic includes carbonates and / or carbides. In sodium-based cells, the sodium ion equivalents of any of these materials may be used.

[0054] In some embodiments, the lithium ion conductive material or sodium ion conductive material may be selected from species capable of donating an electron pair (e.g., Lewis bases). Examples of suitable electron donating materials include, but are not limited to, lithium oxides (e.g., Li2O, LiO, LiO2, LiRO2, where R is scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium, and / or lutetium), lithium carbonate (Li2CO3), lithium nitride (e.g., Li3N), lithium oxysulfide, lithium oxynitride, lithium garnet-type oxides (e.g., Li7La3Zr2O 12 ), Li 10 GeP2S 12 , lithium phosphate nitride, lithium silicate, lithium germanate, lithium lanthanum oxide, lithium titanium oxide, lithium borate, lithium aluminate, lithium phosphosulfide, lithium silicate, lithium borate, lithium aluminate, lithium phosphate, lithium halates, and combinations of the above. Sodium equivalents of the above may also be envisaged.

[0055] Examples of ceramic materials that can be used as lithium ion conductive materials include Li-containing oxides, e.g., Li 3.3 La 0.56 TiO3, Nasicon structure (e.g., LiTi(PO4)3), LiSICON (Li 14 Zn(GeO4)4), Li 10 GeP2S 12 , Garnet, Li7La3Zr2O 12, Li2O, other oxides such as Al2O3, TiO2, ZrO2 SiO2, ZnO, sulfides such as Li2S-P2S5, antiperovskites such as Li3OCl, hydrides such as LiBH4, LiBH4-LiX (X=Cl, Br, I), LiNH, LiNH2, Li3AlH6, Li2NH, borates or phosphates such as Li2B4O7, Li3PO4, LiPON, carbonates or hydroxides such as Li2CO3, LiOH, fluorides such as LiF, nitrides such as Li3N, sulfides such as lithium borate, lithium phosphosulfide, lithium aluminosulfide, oxysulfides, praseodymium oxide. At least one of the ceramic materials may be used, or a combination of them may be used. In sodium-sulfur cells, the sodium ion equivalent of any of these conductive materials may be utilized.

[0056] In some embodiments, the lithium ion conducting material or sodium ion conducting material may be formed of an inherently ionically conducting polymeric material, such as Nafion. Alternatively, the polymer blended with the lithium (or sodium) salt may be formed of a 10 -7Bulk conductivities of greater than 10 ... Examples of suitable polymeric materials include: vinyl fluoride; inorganic polymers (e.g., polysilanes, polysilazanes, polyphosphazenes, polyphosphonates), polyurethanes; polyolefins (e.g., polypropylene, polytetrafluoroethylene); polyesters (e.g., polycarbonate, polybutylene terephthalate). In one embodiment, coblock polymers such as Nafion may be used. At least one of such polymeric materials, or a combination thereof, may be used. In one embodiment, the cathode contains ceramic particles in combination with one or more ion-conducting polymers.

[0057] The electroactive material in the cathode may be present on the current collector in an amount of 60-90 wt%, preferably 65-85 wt%, more preferably 70-80 wt%. The conductive material may be present in the matrix deposited on the current collector in an amount of 10-45 wt%, preferably 15-35 wt%, more preferably 20-25 wt%. The weight ratio of electroactive material to conductive material may be 0.01-10:10-50, preferably 0.1-5:15-45, more preferably 1-5:20-35.

[0058] If a separator is present in the cell, the separator may comprise any suitable porous substrate that allows ions to move between the electrodes of the cell. The separator should be positioned between the electrodes to prevent direct contact between the electrodes. The porosity of the substrate should be at least 30%, preferably at least 50%, for example, greater than 60%. Suitable separators include meshes formed from polymeric materials. Suitable polymers include polypropylene, nylon, and polyethylene. Non-woven polypropylene is particularly preferred. Multi-layer separators can be used.

[0059] Any suitable electrolytic quality may be included in the electrochemical cell. quality Liquid electrolyte quality Electrolysis quality Organic solvents and electrolytic quality The solvent may include salts. Suitable organic solvents include ethers, esters, amides, amines, sulfoxides, sulfamides, organophosphates, ionic liquids, carbonates, and sulfones. Mixtures of one or more solvents may be used. Examples of solvents include ethylene carbonate, dimethyl carbonate, tetrahydrofuran, 2-methyltetrahydrofuran, methylpropyl propionate, ethylpropyl propionate, methyl acetate, 1,2-dimethoxyethane, 1,3-dioxolane, diglyme (2-methoxyethyl ether), triglyme, tetraglyme, butyrolactone, 1,4-dioxane, 1,3-dioxane, hexamethylphosphoramide, pyridine, dimethylsulfoxide, tributyl phosphate, trimethyl phosphate, N,N,N,N-tetraethylsulfamide, and sulfones, and mixtures thereof.

[0060] electrolytic quality The organic solvent may have a viscosity of less than 20 cP, preferably less than 10 cP, more preferably less than 7 cP at 25° C. quality When used in an electrolytic solution, the mixture may have a viscosity of less than 20 cP, preferably less than 10 cP, and more preferably less than 7 cP at 25° C. qualitymay have a viscosity at 25° C. of less than 20 cP, preferably less than 10 cP, and more preferably less than 7 cP.

[0061] Suitable electrolysis quality The salts include lithium or sodium salts. Suitable lithium salts include lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium nitrate, lithium perchlorate, lithium trifluoromethanesulfonimide, lithium bis(oxalate)borate, and lithium trifluoromethanesulfonate. Suitable sodium salts include sodium hexanoate, sodium hexafluoroarsenate, sodium nitrate, sodium perchlorate, sodium trifluoromethanesulfonimide, bis(sodium oxalate)borate, and sodium trifluoromethanesulfonate. Preferably, the lithium salt is lithium trifluoromethanesulfonate (also known as lithium triflate). Combinations of salts may be used. For example, lithium triflate may be used in combination with lithium nitrate. The lithium salt is electrolytically dissolved in a solution at a concentration of 0.1-6M, preferably 0.5-3M, for example 1M. quality It may be present in

[0062] electrolytic quality The battery may also include lithium polysulfide or sodium polysulfide. For example, lithium polysulfide may be electrolytically charged before the cell is discharged. quality It may be added to the electrolytic quality The concentration of lithium polysulfide dissolved in the lithium ion exchange resin can be 0.1% to 20% by weight (preferred concentration is 1.5%). Examples of suitable lithium polysulfides include Li2S n , where n=at least 5, for example, 6 to 15, for example, 8 to 12 (for example, 8). Lithium polysulfide or sodium polysulfide can be electrolytically quality The sulphuric acid may serve to buffer the sulphur content of the electrolyte, increase the capacity of the cell or act as a sulphur source to compensate for any loss of sulphur due to the formation of non-conductive species.

[0063] The cell according to the invention may be provided in a suitable housing. This housing may define the electrochemical zones. Preferably, the housing is flexible, for example a flexible pouch. The pouch may be made of a composite material, for example a composite of metal and polymer. In one embodiment, one or more cells are enclosed in the housing. One or more cells may be sealed in the pouch. A region of each of the one or more cells may protrude from the housing. This region may be bonded to a contact tab, for example made of nickel. The contact tab may be connected to an alkali metal or alkali metal alloy by any suitable method, for example (ultrasonic) welding. Alternatively, the contact tab itself may protrude from the housing. If several electrochemical cells are present in the cell assembly, the respective regions of the anode may be pressed or bonded together to form a pile of anodes that may be connected to the contact tabs.

[0064] The cell according to the invention may be subjected to a force. Preferably, the force is an anisotropic force, i.e. it has different values ​​when measured in different directions. A component of the force is applied, for example, perpendicular to the active surface of the anode of the electrochemical cell. In one embodiment, the force is applied continuously to the cell. In one embodiment, the force is maintained at a specific value. Alternatively, the force may vary over time. The force may be applied over the entire surface of the anode. Alternatively, the force may be applied over a portion of the surface of the anode, for example over at least 80% of the surface, preferably over at least 60% of the surface, preferably over at least 40% of the surface, for example over at least 20% of the surface. The force may be applied directly to the cell. Alternatively, the force may be applied to one or more plates, for example metal plates, located outside the cell or stack of cells. The force may be applied externally to a housing in which one or more cells are contained. For example, one or more cells may be contained within a flexible pouch and the force may be applied externally to the flexible pouch.

[0065] The force may improve the performance of the electrochemical cell. Without wishing to be bound by any theory, it is believed that the pressure applied to the anode allows for maintaining an intimate contact between the protective layer and the alkali metal or metal alloy layer. Applying pressure to the anode may allow for the formation of an alkali metal plating below the protective layer, between the protective layer and the alkali metal / metal alloy. This may avoid or reduce the formation of plating on the protective layer, which may be uneven and may result in cracks or pitting on the surface. If plating occurs below the protective layer, a smooth surface of the anode may be maintained and the formation of cracks or voids on the surface may be reduced. Dendrite formation may then be prevented. Furthermore, the alkali metal deposit located below the protective layer may be electrolytically quality This prevents direct contact with the electrolyte during cycling. quality can be prevented from being reduced, and a decrease in the cycle life of the cell can be avoided.

[0066] In one embodiment, the force may be a clamping force. Alternatively, the force may be a compression force. The clamping force may be applied to the cells using a clamp. Alternatively, one or more clamping elements may be positioned around the outside of the cell or cells. The clamping elements may take the form of a band or tube that surrounds the cell or at least a portion of the exterior of the cell. The band may be made of any suitable material. In one embodiment, the band is formed of an elastic material that may be stretched around the cell or cells and applies a clamping force when in place. In one embodiment, the band is an elastic band. Alternatively, the band may be fastened around the cell or cells. The clamping element may also take the form of a shrink wrap material. In a further arrangement, one or more compression springs may be used, for example, one or more cells may be housed within a containment structure with one or more compression springs located between the containment structure and the cells. Other means of applying the force may include screws or weights.

[0067] One or more of the above methods of applying force may be used. Any suitable force greater than 0 MPa may be used. The force applied to the cell or cells may be in the range of up to 0.5 MPa, preferably up to 2 MPa, such as up to 5 MPa. The force may be at least 0.1 MPa, preferably at least 0.5 MPa, such as at least 1 MPa. The force may be between 0.1 MPa and 5 MPa, preferably between 0.5 MPa and 3 MPa, such as between 1 MPa and 1.5 MPa.

[0068] Also disclosed herein is a method for forming an electrochemical cell including a protective layer as described above. In particular, the protective layer is a metal and / or non-metal that is alloyed with an alkali metal and formed on a current collecting layer, and deposited on a first layer, and -5 S cm -1 The second layer may comprise an ionically conductive layer having an electronic conductivity of less than 100 . According to one aspect of the invention, a method of forming an electrochemical cell assembly including one or more cells as described above is disclosed. According to the invention, the method includes providing a current collecting layer, contacting at least one alloy forming metal and / or non-metal with the current collector to form a first layer, and depositing 10% or more of a cation on a surface of the first layer. -5 Scm -1 and depositing an ionically conductive layer having an electronic conductivity less than 100 nm to form a second layer. Preferably, at least one of the first layer and the second layer is a continuous layer, and more preferably, both the first layer and the second layer are continuous layers.

[0069] Any suitable method may be used to form the first layer. Examples of suitable methods include physical or chemical deposition methods such as physical or chemical vapor deposition. Suitable methods may include plasma enhanced chemical vapor deposition, sputtering, evaporation, electron beam evaporation, and chemical vapor deposition (CVD). These methods may be used to deposit the first layer, for example, on the current collecting layer. Additionally or alternatively, these methods may be used to deposit the second layer of the protective layer on the first layer. Alternative methods of forming the first layer and / or second layer may include inkjet printing, slot die, and spray coating. These methods may be used to apply, for example, the second layer comprising a polymer.

[0070] The following examples are intended only to illustrate the invention and are not intended to limit the scope of the claims in any way. EXAMPLES

[0071] Example 1 Alloy protective layer

[0072] An alloy protective layer was formed on the lithium foil anode. The alloy protective layer was formed by depositing a thin film of indium by sputtering. Figure 2a shows the impedance of a reference anode containing lithium and an anode containing lithium and an indium coating. As can be seen in Figure 2a, the impedance characteristics of the assembled anode with the indium coating are improved compared to the reference anode. However, over time, the indium layer becomes electrolytically quality The lithium reacts with the indium and the resistance increases as seen in Figure 2b. Figure 2c shows significant plating on top of the indium layer and uneven lithium delamination. The formation of voids is observed on the surface of the anode. Example 2

[0073] Ceramic Protective Layer

[0074] A ceramic protective layer containing LiPON was formed on the surface of the lithium electrode. Figure 3a shows the large charge transfer resistance when the ceramic layer was applied. The charge transfer resistance remained stable over time. However, very non-uniform lithium peeling and plating was observed (Figure 3b).

[0075] Example 3

[0076] Combination of alloy layer and LiPON layer

[0077] A force was applied to the lithium anode having a protective layer, first comprising an indium layer on the lithium anode, followed by a LiPON layer on the indium layer. The force was applied by a clamp. Following a single cycle (which involves charging and then discharging the cell, causing peeling and then plating), digital photographs and SEM images (Figure 4) show the extent of lithium plating on the top and bottom of the protective layer. When no force is applied to the lithium anode, lithium is shown to plate on both the top and bottom of the protective layer. In particular, lithium plating is seen on top of the protective layer. At 0.5 MPa, lithium plating is seen on the top and bottom of the protective layer. Compared to 0 MPa, it is clear that there is less lithium plating on the top of the protective layer. When a larger force of 1 MPa is applied, lithium is mostly plated on the bottom of the protective layer, and only a very small area of ​​lithium plating is seen on the top of the protective layer. For the lithium plating step, 4 mA hcm -1 This is roughly equivalent to forming a 20 μm-thick lithium layer underneath the protective layer at 1 MPa.

[0078] FIG. 5 shows a protected lithium anode having a protective layer first with an indium layer on the lithium anode, followed by a LiPON layer on the indium layer, after lithium plating followed by cycles of peeling at 0.5 MPa and 1 MPa forces. The surface of the protected lithium appears pristine and smooth. No significant defects or voids are evident, and any cracks or thickness variations can be attributed to sample processing rather than uneven lithium plating. The peeled electrode shows uniform peeling of the electrode without substantial pitting and / or cracking. FIG. 6 shows the impedance characteristics of the protected lithium anode compared to bare lithium anodes and lithium anodes with only a LiPON layer. A drop in impedance is evident for the protected lithium anode.

[0079] Example 4 Pouch cell with protected lithium anode

[0080] A lithium pouch cell was constructed with a protected lithium anode having a protective layer that first comprised a layer of indium on the lithium anode, followed by a layer of LiPON on the indium layer. The pouch cell was a symmetric pouch cell containing two protected lithium electrodes, one acting as the working electrode and the other as the counter / reference electrode. Each protected lithium electrode had a length of 33.6 cm. 2 Figure 7 provides electrochemical data for the pouch cell over several cycles, where the cell was powered at 0.4 mA cm -2 Charged / discharged at 4mA hcm per step -2 A charge of 1 MPa was passed through the pouch cell during cycling. A pressure of 1 MPa was applied to the pouch cell. Figure 7 also provides electrochemical data for a comparative cell in which a bare lithium foil anode was used, and a further comparative cell in which a bare lithium foil anode was used but no pressure was applied to the cell. Improved cycling is seen for the lithium pouch cell which constitutes a protected anode. Cycling of the cells containing the bare lithium foil anode was stopped at 25 cycles (reference cell) and 60 cycles (applied pressure), respectively, when a short circuit was observed.

[0081] Throughout this description and the claims, the terms "comprise" and "contain" and variations thereof mean "including but not limited to" and they are not intended to (and do not) exclude other moieties, additives, ingredients, integers or steps. Throughout this description and the claims, the singular encompasses the plural unless the context requires otherwise. In particular, when the indefinite article is used, the specification should be understood as contemplating the plural as well as the singular, unless the context requires otherwise.

[0082] It should be understood that any feature, integer, property, compound, chemical moiety or group described in connection with a particular aspect, embodiment or example of the invention is applicable to any other aspect, embodiment or example described herein, unless incompatible therewith. All of the features disclosed in this specification (including any accompanying claims, abstract and drawings), and / or all of the steps of any method or process so disclosed, may be combined in any combination, except combinations in which at least some of such features and / or steps are mutually exclusive. The invention is not limited to the details of any of the foregoing embodiments. The invention extends to any novel one or any novel combination of features disclosed in this specification (including any accompanying claims, abstract and drawings), or any novel one or any novel combination of steps of any method or process so disclosed.

Claims

1. 1. An electrochemical cell assembly comprising: At least one or more electrochemical cells, a cathode comprising an electrochemically active material; - an anode comprising an alkali metal or alkali metal alloy layer and a protective layer comprising a first layer and a second layer, the first layer comprising a metal and / or a non-metal that alloys with the alkali metal being formed on the alkali metal or alkali metal alloy layer, the second layer being deposited on the first layer, the second layer being less than 10 -5 S.C.M. -1 an anode, an ionically conductive layer having an electronic conductivity of less than 1000 nm, wherein the total amount of alkali metal that can be stored in said first layer is less than 60% of the electrochemical alkali metal storage capacity of the electroactive material in said cathode; at least one or more electrochemical cells comprising an electrolyte, The cell assembly further comprising a means for applying pressure to the at least one or more electrochemical cells.

2. 2. The electrochemical cell assembly of claim 1, wherein the alkali metal or alkali metal alloy comprises lithium metal or a lithium metal alloy or sodium metal or a sodium metal alloy.

3. The electrochemical cell assembly of claim 1 , wherein the anode further comprises a current collector.

4. 4. The electrochemical cell assembly of claim 1, wherein the first layer comprises at least one metal or non-metal selected from aluminum, boron, zinc, gallium, indium, carbon, silicon, germanium, tin, lead, antimony, silver, gold, sodium, potassium, magnesium, calcium, and mixtures thereof.

5. The first layer is 10 -5 S.C.M. -1 5. The electrochemical cell assembly of claim 1, having an electronic conductivity of greater than 0.

1.

6. The first layer is subjected to 10 -15 cm 2 s -1 6. The electrochemical cell assembly of claim 1, having a lithium diffusivity of greater than

7. The first layer is 10 -9 S.C.M. -1 7. The electrochemical cell assembly of claim 1, having a greater ionic conductivity.

8. The electrochemical cell assembly of any one of claims 1 to 7, wherein the first layer has a thickness of from 1 nm to 5000 nm.

9. The electrochemical cell assembly of any one of claims 1 to 8, wherein the second layer comprises at least one of a ceramic material, a polymeric material, a composite material of polymer and ceramic, and combinations thereof.

10. 10. The electrochemical cell assembly of claim 1, wherein the second layer comprises an oxynitride, sulfide, phosphate, oxide, oxysulfide, thiophosphate, borate, oxyborate, borohydride, silicate, aluminate, or thioaluminate compound, or a combination thereof.

11. 10. The electrochemical cell assembly of claim 9, wherein the ceramic material is LiPON.

12. 10. The electrochemical cell assembly of claim 9, wherein the polymeric material is polyethylene oxide.

13. The second layer is 10 -9 S.C.M. -1 13. The electrochemical cell assembly of any one of claims 1 to 12, having a greater ionic conductivity.

14. 14. The electrochemical cell assembly of claim 1, wherein the second layer has a thickness of from 1 nm to 1000 nm.

15. 15. The electrochemical cell assembly of any one of claims 1 to 14, wherein the total amount of alkali metal capable of being stored in the first layer is less than 10% of the electrochemical alkali metal storage capacity of an electroactive material in the cathode.

16. 16. The electrochemical cell assembly of any one of claims 1 to 15, wherein the means for applying pressure comprises a band, wrap, or tube positioned on the outside of the cell.

17. 17. The electrochemical cell assembly of any one of claims 1 to 16, wherein the at least one or more cells are selected from lithium-sulfur or sodium-sulfur cells, lithium-air or sodium-air cells, or lithium-ion or sodium-ion cells.

18. A method of forming an electrochemical cell assembly according to any one of claims 1 to 17, said method comprising: a) providing an alkali metal or alkali metal alloy layer; b) contacting the alkali metal or alkali metal alloy layer with at least one metal and / or nonmetal that forms an alloy with an alkali metal to form a continuous first layer; c) 10 on the surface of the first layer -5 S.C.M. -1 and depositing an ionically conductive layer having an electronic conductivity less than 100 nm to form a continuous second layer, wherein steps a) through c) form an anode; d) providing an electrolyte; e) providing a cathode, wherein steps a) through e) form an electrochemical cell; f) applying a means for providing a force to at least one cell formed according to steps a) to e).

19. 20. The method of claim 18, wherein at least one of the first layer and the second layer is formed by physical vapor deposition.

Citation Information

Patent Citations

  • Lithium negative electrode for electrochemical cells

    JP2003515892A

  • Storage battery

    JP2006310033A

  • Coated lithium electrodes

    US6537701B1